Magnetic field energy harvesting from the traction return current in rail tracks. (15th June 2021) - Kuang, Yang; Chew, Zheng Jun; Ruan, Tingwen; Lane, Tim; Allen, Ben; Nayar, Bimal; Zhu, Meiling
Highlights: Traction return current is a promising source for railway energy harvesting. A magnetic core partially enclosing the rail track can increase the power output. The optimal design should trade effective permeability against eddy current loss. Nonlinear magnetization and magnetic saturation leads to increased optimal load. The harvester produced average power of 5.05 W under a rail current of 520 A. Abstract: Alternating magnetic fields generated by AC traction return currents in rail tracks are an untapped energy source that can be scavenged by a magnetic field energy harvester (MFEH) to power wireless condition monitoring sensors. This paper reports the first comprehensive study on the design, optimisation and experimental testing of such MFEH. The magnetic core has been specially designed with two flux collectors partially enclosing the rail track to increase the power output. An electromagnetic-circuit coupled finite element model (FEM) has been developed to optimise the design under the influence of eddy current loss in the rail track, which has not been investigated before. The simulation reveals that an optimal design should trade off the effective permeability against the eddy current loss, instead of purely maximising the effective permeability as in previous studies. The effects of the various design parameters on the performance of the MFEH have been investigated to obtain an optimised design. An optimised design has been prototyped and tested under a section of current-carrying rail track. The experimental results showed good agreements with simulations. Experimental results show that nonlinear magnetization and magnetic saturation has negatively affected the power generation but the effect can be minimised by increasing the load resistance. The MFEH has produced average power of 5.05, 3.5 and 1.6 W, when placed at 48, 95, 190 mm from the rail track carrying 520 A at 50 Hz, respectively. The power generated has a significant potential for powering wireless sensors for a range of railway monitoring applications.